The study of volatile oil of Foeniculum vulgare Miller. In their tissue culture and comparison with the whole plant - MR Shams Ardekani; A Hadjiakhoondi; AH Jamshidi; Kh Abdi (Institue of Medicinal Plants, ACECR, 2005)
Background: Foeniculum vulgare Miller. is a traditional herbal medicine used widely in world. This paper focuses on the analysis of the chemical composition of essential oil from the whole plant and calli of Foeniculum vulgare Miller.. Method: Growing the calli of Foeniculum vulgare Miller. and production its secondary metabolites studied and compared with those in the whole plant. Seeds were immersed in water for 5 min, surface-sterilized in 70% aqueous ethanol for 2 min and rinsed three laid on autoclaved agar (0.8%) and after 10 days the upper parts of the resultant seedlings were transferred to autoclaved MS (Murashige and Skoog) basal medium which were containing 2,4- D (1 mg/l), IAA (1 mg/l) and K (0.2 mg/l) as plant grow regulators. The callus were produced and subcultvred every 20-22 days. Results: Callus volatile constituents were consisted of monoterpene hydrocarbons (14.13%) and oxygenated monoterpenes (34.83%) the typical components were (E, E) 2,4 - Decadienal (22.64%) and 1,8 cineole (17.35%). In the whole plant 37 major compounds were detected in the oild totally 91.37 to 96.93% of the essences were consisted of these compoundes. E Anethole, Estragole and D-(+)- Fenchone were the most frequent compounds.